1993
DOI: 10.1029/92tc00618
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical role of backstops in the growth of forearcs

Abstract: We use numerical and laboratory modeling to analyze the mechanical role of backstops in the overriding plate at subduction zones. A backstop is defined as a region within a forearc that has significantly greater shear strength than the sediment lying farther trenchward; it can be thought of as the bulldozer behind an accretionary wedge. We calculate the stress and displacement fields within forearcs for various backstop models using the finite element method, and we simulate deformation over a backstop using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
1
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 42 publications
10
103
1
3
Order By: Relevance
“…12d, e), which has produced the best antiformal stack simulation, demonstrates that its formation requires some amount of backstop-edge effects. This fact confirms the analysis made by Byrne et al (1993) about backstops within a forearc at subduction zones. They concluded that backstops are stronger than the rocks lying further trenchwards, deform little but may influence the kinematics of the trench rocks.…”
Section: Discussionsupporting
confidence: 79%
“…12d, e), which has produced the best antiformal stack simulation, demonstrates that its formation requires some amount of backstop-edge effects. This fact confirms the analysis made by Byrne et al (1993) about backstops within a forearc at subduction zones. They concluded that backstops are stronger than the rocks lying further trenchwards, deform little but may influence the kinematics of the trench rocks.…”
Section: Discussionsupporting
confidence: 79%
“…The wedge is bounded to the rear by a region that is deforming less rapidly or not at all, known as the backstop [Byrne et al, 1993]. The backstop may be rigid, or the lack of deformation may be a result of high elevation, such that the loads generated by the topography roughly equal those exerted on its boundaries.…”
Section: The Physical Basis Of the Analysismentioning
confidence: 99%
“…The use of backstops with finite height resulted in significantly different wedge geometries [e.g., Malavieille, 1984;Byrne et al, 1993;Willet et al, 1993;Koons, 1989Koons, , 1990, although the deformation mechanism remained the same (Figure lb). The frontal part (or prowedge) still behaves as in the minimum tapered bulldozer model (Figure la), but differences occur to the rear above the tip of the backstop.…”
Section: Introductionmentioning
confidence: 99%